Optimizing Self-Care Management for Psoriasis Patients in Limited Population: Utilizing WhatsApp - Sari, Dewi Purnama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Psoriasis is a chronic disease characterized by skin cell proliferation and inflammation which can greatly impact the individual quality of life. Generally, people with Psoriasis may not realize they have the condition until it becomes severe (flare up). Individuals residing in communities or areas with access to dermatological care may face challenges in receiving accurate diagnoses. Utilizing communication technology, like WhatsApp for self care management education could significantly impact enhancing their quality of life. This community service assess the effectiveness of using instant messaging technology (WhatsApp) for educating Psoriasis patients. The method focusing on education utilizing through WhatsaApp. Result has noted a improve Dermatology Life Quality Index (DLQI) scores. While the initiative was carried out with a limited group of Psoriasis the outcomes suggest a possibility for expansion on a level to other chronic disease.